Stabilization of level of reliability of dangerous operated manufacture complexes by means of simulation modeling - Maksimey, Иван Васильевич; Smorodin, В. С. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
About the possibility of organization of governing by technological process of realtime manufacture by means of complex of imitation is reported. The technology of governing by manufacture process and strategy of checking of system indicators are stated.